Spatial variation of residential land uses and needs assessment in Adhamiya district center using GIS (Journal of the College of Basic Education, 2023)
For the purpose of determining the cadastral changes in land use in the study area, reliance was made on the data of the relevant departments and institutions, Through the use of some statistical methods for the results of the field survey, such as the method of analysis using the Pearson and Spearman laboratories and the Ka2 square and the linear-linear test with the aim of arriving at determining the most important characteristics of spatial variation for residential use according to the residential neighborhoods of the study area. characteristics. The study relied on clarifying this on a set of tables, statistical techniques, maps and graphical forms to highlight the phenomenon of change and clarify it accurately. The study was to change the land uses and the urban situation in terms of building areas and the urban description of its urban development, and the distinctive planning and design elements for it to determine the level of changes taking place in it